ANALISIS MEMORI SASTRA DALAM NOVEL SALAH ASUHAN KARYA ABDOEL MOEIS - Alfiana Firazma; Maulina Nur Choirunisa; Aulia Azzahra; Muhammad Aditya Surya Saputra (KOLASE, 2022)
This study aims to find out how the literary memory of the characters contained in the short story Salah Asuhan by Abdoel Moeis. Research using descriptive qualitative method. With the research instrument in the form of the Short Story of Wrong Upbringing by Abdoel Moeis. The analysis technique used is read-note. The research step, namely the researcher first reads the Novel Salah Asuhan, then after reading the novel. The researcher analyzes how the memories are contained in each of the characters. There are five figures analyzed based on memory, namely Hanafi, Corrie de Busse, Ms. Hanafi, Rapiah, and Corrie’s father (Mr. De Busse). The results of the study show that there are different memories or memories for each character, be it Hanafi, Corrie, Ms. Hanafi, Rapiah, and Corrie’s father (Mr. De Busse).